Efektivitas Media Digital Grok.ai dan Canva Mitigasi Longsor dalam Meningkatkan Keterampilan Menyimak Kelas 3 - Nadia Ramadhani Islamiyah Bakri; Nurul Istiq’faroh; Rasya Junesta Alzara; Jihan Putri Nuriyanti (Journal of Contemporary Issues in Primary Education, 2026)
This research is motivated by the low listening skills of elementary school students caused by the lack of use of interesting and interactive learning media. In addition, the importance of early landslide disaster mitigation education is also a concern in learning. This study aims to describe the development process and determine the effectiveness of digital media based on Grok.ai and Canva in improving the listening skills of third-grade elementary school students. This study used a descriptive quantitative method with a one-group pretest-posttest design. The research subjects were 22 students. Data collection techniques were carried out through pretest and posttest tests, then analyzed using normality tests, paired sample t-tests, and N-Gain calculations. The results showed that the average pretest score of 56.97 increased to 83.64 in the posttest. The t-test results showed a significance value <0.05, indicating a significant difference, and the N-Gain value of 0.6617 is in the moderate category. Thus, digital media based on Grok.ai and Canva are effective in improving students' listening skills. This research has implications for the use of AI-based technology in innovative learning and has the potential to be developed into other materials.